2019
DOI: 10.1111/nep.13549
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotic supplements on the progression of chronic kidney disease: A meta‐analysis

Abstract: Background Chronic kidney disease (CKD) is a worldwide public health problem. Although accumulated data suggested that probiotic supplements played roles in CKD, the results remained controversial. Here, we performed a meta‐analysis to assess the effects of probiotic supplements on the CKD progression. Methods A systematic search was conducted through the PubMed, Embase and Cochrane databases until September 2018. Randomized controlled trials with control receiving placebo, evaluating the effects of probiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 48 publications
(141 reference statements)
2
21
0
Order By: Relevance
“…Similarly, another RCT-based meta-analysis of probiotics in CKD control revealed more promising results to manage urea levels in non-dialysis CKD patients. On the other hand, no significant change in glomerular filtration rate, uric acid, serum creatinine, and C-reactive protein concentrations were found ( Tao et al, 2019 ).…”
Section: Health-boosting Spectrum Of Probioticsmentioning
confidence: 99%
“…Similarly, another RCT-based meta-analysis of probiotics in CKD control revealed more promising results to manage urea levels in non-dialysis CKD patients. On the other hand, no significant change in glomerular filtration rate, uric acid, serum creatinine, and C-reactive protein concentrations were found ( Tao et al, 2019 ).…”
Section: Health-boosting Spectrum Of Probioticsmentioning
confidence: 99%
“…The age-standardized global prevalence of CKD in adults aged 20 and older was 10.4% in men and 11.8% in women [18]. This disease, which is considered a public health problem [19], results in sufferers having to use renal replacement therapy to substitute the renal function. There are currently two dialytic techniques available: hemodialysis and peritoneal dialysis [20].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [85] reported that supplementation with Lactobacillus DM9218 decreases serum uric acid in fructose-fed mice; the authors suggested that it may protect against high-fructose-induced liver damage and retinol uric acid accumulation by degrading inosine. The uric acid level was also significantly reduced in non-dialysis patients with CKD who received probiotics [86]. Moreover, the eight-week consumption of L. gasseri PA-3 yoghurt was found to decrease the level of serum uric acid in 25 patients [87].…”
Section: The Effects Of Probiotics Prebiotics and Synbiotics On Uric Acid Levelsmentioning
confidence: 91%